Effect of benzylaminopurine (BAP) on clonal propagation rate of Curcuma longa L. - Mogor, A. F. [UNESP]; Mogor, G. [UNESP]; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (My University, 2004)
Curcuma longa L. is used in many countries for its flavor, and medicinal and cosmetic attributes, as well as for its peculiar starch characteristics. These factors have driven an interest in the in vitro propagation of this species, looking for germplasm bank maintenance, production of disease free plants, genetic variability induction from callus, and as a tool for starch research. However, there are few reports concerning the micropropagation of Curcuma longa. The in vitro propagation rate of this species, cultured under two benzylaminopurine (BAP) concentrations, was the aim of this research.
Keywords: Benzylaminopurine (BAP); Clonal propagation; Curcuma longa L.; Cytokinin; Tissue culture